2021
DOI: 10.1371/journal.ppat.1009723
|View full text |Cite
|
Sign up to set email alerts
|

ACE2-lentiviral transduction enables mouse SARS-CoV-2 infection and mapping of receptor interactions

Abstract: SARS-CoV-2 uses the human ACE2 (hACE2) receptor for cell attachment and entry, with mouse ACE2 (mACE2) unable to support infection. Herein we describe an ACE2-lentivirus system and illustrate its utility for in vitro and in vivo SARS-CoV-2 infection models. Transduction of non-permissive cell lines with hACE2 imparted replication competence, and transduction with mACE2 containing N30D, N31K, F83Y and H353K substitutions, to match hACE2, rescued SARS-CoV-2 replication. Intrapulmonary hACE2-lentivirus transducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(92 citation statements)
references
References 144 publications
(235 reference statements)
6
86
0
Order By: Relevance
“…These results show that exposure to SARS-CoV-2 is highly immunogenic even when the lack of hACE2 expression prevents productive SARS-CoV-2 infection and that hACE2 expression via lentiviral transduction does not trigger a significant immune response. These data support previous evidence that that exposure to SARS-CoV-2 is significantly more immunogenic than lentiviral transduction [19]. Thus, this model could be implemented as a simple methodology to generate mice models for SARS-CoV-2 infections.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These results show that exposure to SARS-CoV-2 is highly immunogenic even when the lack of hACE2 expression prevents productive SARS-CoV-2 infection and that hACE2 expression via lentiviral transduction does not trigger a significant immune response. These data support previous evidence that that exposure to SARS-CoV-2 is significantly more immunogenic than lentiviral transduction [19]. Thus, this model could be implemented as a simple methodology to generate mice models for SARS-CoV-2 infections.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we characterized the effects of SARS-CoV-2 infection on Lenti-hACE2transduced IFNAR1 −/− mice models, to achieve a more efficient SARS-CoV-2 infection and produce higher viral loads compared to wild-type mice. These mice were sensitized to SARS-CoV-2 infection by lentivirus-mediated hACE2 expression [19], as confirmed both in vitro and in vivo by detection of viral RNA, viral proteins, and infectious virion production (Figures 1-4). RNA-seq analysis of SARS-CoV-2-infected IFNAR1 −/− C57BL6 mice lungs showed that lentiviral-mediated hACE2 expression does not measurably activate cellular antiviral mechanisms, which could potentially inhibit subsequent SARS-CoV-2 infection [19].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations